Adjusting to Global Change through Clonal Growth and Epigenetic Variation - Dodd, Richard S.; Douhovnikoff, Vladimir (Frontiers in Ecology and Evolution, 2016)
The earth is experiencing major changes in global and regional climates and changes are predicted to accelerate in the future. Many species will be under considerable pressure to evolve, to migrate, or be faced with extinction. Clonal plants would appear to be at a particular disadvantage due to their limited mobility and limited capacity for adaptation. However, they have outlived previous environmental shifts and clonal species have persisted for millenia. Clonal spread offers unique ecological advantages, such as resource sharing, risk sharing, and economies of scale among ramets within genotypes. We suggest that ecological attributes of clonal plants, in tandem with variation in gene regulation through epigenetic mechanisms that facilitate and optimize phenotype variation in response to environmental change may permit them to be well suited to projected conditions.